Psychological distress and associated factors among healthcare professionals in Ethiopia during the COVID-19 pandemic: a cross-sectional study. Issue 7 (28th July 2022) - Demilew, Demeke; Angaw, Dessie Abebaw; Getnet, Berhanie; Tesfaye, Bizuneh; Atnafu, Asmamaw; Andualem, Zewudu; Kerebih, Habtamu
Abstract : Objectives: The objective of the study was to assess psychological distress (depression, anxiety and stress) and associated factors among healthcare professionals working at the University of Gondar Comprehensive Specialized Hospital, Ethiopia. Design: Institution-based cross-sectional study. Setting: This study was conducted at the University of Gondar Comprehensive Specialized Hospital. Participants: Study participants were healthcare professionals from University of Gondar Comprehensive Specialized Hospital. They were selected for the study using a stratified sampling technique. Measurement: Data were collected using a self-administered questionnaire. The 21-item Depression, Anxiety and Stress Scale was used to assess the depression, anxiety and stress levels. Descriptive and analytical statistics were used to present the findings. To determine the predictor variables for depression, anxiety and stress, a binary logistic regression model was fitted. Finally, variables with p value <0.05 in the final model were declared as significantly associated with psychological distress. Result: Almost half (49.5) of the participants have psychological distress. The prevalence of depression, anxiety and stress during the COVID-19 pandemic among healthcare workers was 167 (42.7%), 201 (51.4%) and 242 (61.9%), respectively. In multivariable analysis, respondents found in the ages between 35 and 44; unmarried marital status; educational status with specialty, subspecialty and PhD holders; anaesthesia professionals; and healthcare professionals with known medical illness were significantly associated with depression. Unmarried marital status, anaesthesia professional, laboratory technologist and living with family were significantly associated with anxiety. Unmarried marital status; educational status with specialty, subspecialty and PhD holders; and anaesthesia professional were also statistically significant with stress. Conclusion and recommendation: The prevalence of depression, anxiety and stress during the COVID-19 pandemic among the Gondar University healthcare professionals was high. This could contribute to implementation of mitigation measures in a standardised and sustainable manner and emphasis should be given to this aspect of health even for future similar and unanticipated events.